Proposed Business Strategy to Increase Sales - Tama, Widya; Wandebori, Harimukti (Almana : Jurnal Manajemen dan Bisnis, 2024)
Opening a coffee shop is one of Indonesia's most popular business ventures, driven by the nation's growing coffee culture. However, coffee shop owners face challenges in developing effective strategies to sustain their businesses, ensuring consistent revenue, positive customer feedback, and steady product sales. Bagi Kopi has quickly expanded its presence with multiple branches across various cities. Despite its rapid growth, there is a significant disparity in sales performance between branches, with the Yogyakarta branch underperforming compared to Bandung. This study aims to propose a business strategy to boost sales at Bagi Kopi, focusing on the Yogyakarta and Bandung branches. Utilizing a comprehensive root cause analysis through internal and external tools. The study employs a mixed-methods approach, integrating both quantitative data from customer questionnaires and qualitative insights from semi-structured interviews with Bagi Kopi stakeholders. The findings indicate that differences in customer demographics, preferences, and market conditions between Yogyakarta and Bandung significantly impact sales outcomes. Based on these insights, the study proposes targeted strategies for Bagi Kopi in Yogyakarta, focusing on enhancing customer engagement, improving service quality, and leveraging local market opportunities. The proposed strategy includes specific actions such as marketing initiatives, regular staff training, and effective facility management to align the Yogyakarta branch’s performance with that of Bandung.